Highly Sensitive Simultaneous Stripping Voltametric Detection of Zn2+, Cd2+ and Hg2+ by Bismuth Codeposition Procedure with Graphdiyne−Modified Electrode - Yijing Ai; Lisi Wang; Wanting Fu; Xiang Ye; Juan Zhou; Xiaoping Zhang; Shuhai He; Wei Sun (Chemosensors, 2023)
In this paper, graphdiyne (GDY)−modified glassy carbon electrode was prepared and further used for the sensitive and simultaneous detection of three target heavy metal ions of Zn2+, Cd2+ and Hg2+ by codeposition with Bi3+ in the mixture solution. GDY−modified electrodes exhibit a larger electrode area and abundant active sites, which is favorable for absorbing more metal ions. Bismuth has low toxicity and can form alloys with zinc, cadmium and mercury. Therefore, three kinds of heavy metal ions can be pre-concentrated with bismuth on the GDY−modified electrode surface, and the following stripping analysis results in high sensitivity and selectivity. By using differential pulse anodic stripping voltammetry, the detection ranges of Zn2+, Cd2+ and Hg2+ were from 2.0 to 100.0 μM with low detection limits of 0.255 μM, 0.367 μM and 0.796 μM, respectively. In addition, the sensor showed excellent repeatability, reproducibility, and stability, which was applied to sensitive analysis of river water samples with satisfactory results.